Blues Musicians of the Mississippi Delta - Manheim, Steven (Arcadia Publishing Inc., 2019)
The Mississippi Delta blues run as deep and mysterious as the beautiful land from where the music originates. Blues legends B.B. King, Muddy Waters, John Lee Hooker, Howlin' Wolf, Sonny Boy Williamson, and countless other greats came from this region. The Delta blues, born as work songs in Mississippi cotton fields, was played on city street corners and in rural juke joints. With the Great Migration of African Americans in the first half of the 20th century, the Delta blues also made its way from Mississippi to Chicago. The sound of the blues would become the blueprint for the birth of rock and roll in Memphis in the 1950s. The era of the great Delta blues musicians is over, but their legacy remains an important chapter in American music. This book contains images of these important performers and the rich Delta landscapes that influenced their music. -- Amazon.